2022-RA-249-ESGO Overall survival results from ariel3: a phase 3 randomised, double-blind study of rucaparib vs placebo following response to platinum-based chemotherapy for recurrent ovarian carcinoma. (20th October 2022) - Coleman, Robert L; Oza, Amit M; Lorusso, Domenica; Aghajanian, Carol; Oaknin, Ana; Dean, Andrew; Colombo, Nicoletta; Weberpals, Johanne I; Clamp, Andrew R; Scambia, Giovanni; Leary, Alexandra; Holloway, Robert W; et al.
Abstract : Introduction/Background: In ARIEL3 (NCT01968213 ), progression-free survival (PFS) improved significantly with rucaparib maintenance treatment versus placebo. We present updated PFS2 and preplanned final overall survival (OS) analyses. Methodology: ARIEL3 enrolled patients with platinum-sensitive, high-grade ovarian carcinoma who had received ≥2 previous platinum-based chemotherapy regimens and had responded to their last platinum-based regimen. Patients were randomised 2:1 to receive rucaparib 600 mg twice daily or placebo, with 3 protocol-defined nested cohorts: BRCA-mutant, homologous recombination deficient (HRD) and intent-to-treat (ITT). Efficacy outcomes for the nested cohorts included the secondary endpoint of OS (with analysis planned after 70% of events) and the exploratory endpoint of PFS2 (defined as time from randomisation to second event of investigator-assessed disease progression or death due to any cause). Patients were followed for the incidence of myelodysplastic syndrome (MDS) and acute myeloid leukaemia (AML). Data cutoff dates were 31 December 2019 (safety), 4 April 2022 (efficacy) and 12 April 2022 (monitoring of MDS/AML). Results: After a median follow-up of 77.0 months in the ITT population, 410/564 (72.7%) of OS events had occurred. OS and PFS2 are presented in table 1 . A PARP inhibitor was administered as subsequent treatment to ≈45% of patients who received placebo. Safety data were consistent with those of prior reports. MDS/AML was reported in 14 (3.8%) and 6 (3.2%) patients in the rucaparib and placebo arms, respectively ( P= 0.72). Among these, 8 patients in the rucaparib arm and 6 in the placebo arm developed MDS/AML after completion of study drug treatment. Conclusion: These data support the use of rucaparib as a maintenance treatment for recurrent ovarian carcinoma. Although no OS benefit was observed, the PFS benefit for rucaparib was maintained through the next subsequent line of therapy.